Insight into the bZIP gene family in Lagenaria siceraria: Genome and transcriptome analysis to understand gene diversification in Cucurbitaceae and the roles of LsbZIP gene expression and function under cold stress - Wang, Jian; Wang, Ying; Wu, Xinyi; Wang, Baogen; Lu, Zhongfu; Zhong, Liping; Li, Guojing; Wu, Xiaohua (Frontiers in Plant Science, 2023)
The basic leucine zipper (bZIP) as a well-known transcription factor family, figures prominently in diverse biological and developmental processes and response to abiotic/biotic stresses. However, no knowledge of the bZIP family is available for the important edible Cucurbitaceae crop bottle gourd. Herein, we identified 65 putative LsbZIP genes and characterized their gene structure, phylogenetic and orthologous relationships, gene expression profiles in different tissues and cultivars, and responsive genes under cold stress. The phylogenetic tree of 16 released Cucurbitaceae plant genomes revealed the evolutionary convergence and divergence of bZIP family. Based on the specific domains, LsbZIP family were classified into 12 clades (A–K, S) with similar motifs and exon-intron distribution. 65 LsbZIP genes have undergone 19 segmental and two tandem duplication events with purifying selection. The expression profiling of LsbZIP genes showed tissue-specific but no cultivar-specific pattern. The cold stress-responsive candidate LsbZIP genes were analyzed and validated by RNA-Seq and RT-PCR, providing new insights of transcriptional regulation of bZIP family genes in bottle gourd and their potential functions in cold-tolerant variety breeding.